2018
DOI: 10.1107/s2052252518015129
|View full text |Cite
|
Sign up to set email alerts
|

Biological single-particle imaging using XFELs – towards the next resolution revolution

Abstract: Better injectors resulting from careful iterative optimization used at high repetition XFELs in combination with better detectors and further developed algorithms might, in the not so distant future, result in a ‘resolution revolution’ in SPI, enabling the molecular and atomic imaging of the dynamics of biological macromolecules without the need to freeze or crystallize the sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Currently, the European XFEL is the only facility worldwide to enable experiments at megahertz repetition rates. This unprecedented data collection rate together with submicrometre beam focusing (Bean et al, 2016; and the application of either cage-based reaction initiation (Bourgeois & Weik, 2009;Duke et al, 1992;Schlichting et al, 1990;Stoddard et al, 1998;Tosha et al, 2017) or mix-on-demand sample delivery (Beyerlein et al, 2017;Ishigami et al, 2019;Knoška et al, 2020;Kupitz et al, 2017;Oberthuer et al, 2017;Schmidt, 2013;Stagno et al, 2017;Wang et al, 2014) will allow researchers to trigger and film chemical reactions in rapid time-resolved experiments to obtain threedimensional movies of the nanoworld.…”
Section: Experiments In Structural Biologymentioning
confidence: 99%
“…Currently, the European XFEL is the only facility worldwide to enable experiments at megahertz repetition rates. This unprecedented data collection rate together with submicrometre beam focusing (Bean et al, 2016; and the application of either cage-based reaction initiation (Bourgeois & Weik, 2009;Duke et al, 1992;Schlichting et al, 1990;Stoddard et al, 1998;Tosha et al, 2017) or mix-on-demand sample delivery (Beyerlein et al, 2017;Ishigami et al, 2019;Knoška et al, 2020;Kupitz et al, 2017;Oberthuer et al, 2017;Schmidt, 2013;Stagno et al, 2017;Wang et al, 2014) will allow researchers to trigger and film chemical reactions in rapid time-resolved experiments to obtain threedimensional movies of the nanoworld.…”
Section: Experiments In Structural Biologymentioning
confidence: 99%
“…The aerosol injector reduces the amount of liquid around the sample during sample delivery, thereby the background scanning can be reduced effectively. However, the disadvantage of aerosol injectors is the low hit rate, which is a feature that needs to be optimized .…”
Section: Instrumentation Of Sample Delivery Systemsmentioning
confidence: 99%
“…FEL radiation can be used to gather information on several kinds of biological samples. Biological single particle imaging is one of the main topics of FEL research with dedicated beamlines, although the FEL intensity, the available detectors, and techniques to introduce the sample into the focused X-ray sampling position, were all insufficient to obtain (near) atomic resolution structural information from single biological macromolecules [11]. Nevertheless, recent experiments performed at LCLS showed that single-shot diffraction patterns from biological samples as small as 70 nm in diameter (e.g., the enterobacteria phage PR772 [12,13]) can be measured, and still at LCLS signal up to 5.9Åresolution was observed from rice dwarf virus [14].…”
Section: Coherent Imaging Of Biological Samplesmentioning
confidence: 99%